Vegetation and prominent flora from Begnash Tal to Tara Hill, Annapurna Conversation Area Project, Kaski district - Poudel, S. (Himalayan Journal of Sciences, 2006)
An investigation of vegetation and prominent flora from Begnash to Tara Hill (a very popular trekking route of Annapurna Conservation Area) was carried out. The vegetation is exposed to different levels of human-induced disturbances. The route followed ascends gradually from Begnas passing through different vegetated areas. The altitude of the study area ranges from 1000 to 3000 masl. The vegetation of the study area comprises different types of forests such as hill sal (Shoresa robusta), Schima-Castanopsis, alder, lower temperate mixed broad leaved forest, oak, upper temperate – mixed broad-leaved, Rhododendron, Betula utilis, pine and juniper and arid bushes. Schima wallichii, Castanopsis indica, Quercus semecarpifolia, Rhododendron arboreum, Ilex dipyrena, Pandanus nepalensis, Daphne bholua, Lithocarpus pachyphylla, Pterocarpus santalinus, etc. are the prominent flora of the study area. Himalayan Journal of Sciences 1(1): 43-46, 2003